Concept and Classification of Functions of State Policy in the Field of Ensuring Economic Security of the State - D. O. Koshikov (Law and Safety)
The phenomenon of the state’s functions as the main directions of its activity for the fulfillment of tasks and the purpose of its existence in a specific period of development, their peculiarities and types have been studied. Based on the analysis of scientific works on the implementation of state policy in the sphere of economy and social and humanitarian sphere, the author has defined own definition of the functions of state policy in the sphere of economic security. In particular, the author has emphasized that they could be considered, first of all, as general directions of the state’s activity to create a stable economic security system, which includes a legal framework, a list of agencies authorized to implement regulatory requirements, a system of defined principles, forms and methods of implementation policies, etc; and, secondly, as separate groups of homogeneous actions of public administration subjects on the regulation, development and protection of social economic relations, ensuring the realization of socio-economic rights and freedoms of citizens, as well as creating conditions for further development and growth of the national economy.